Patterns of plant species composition of a temperate floodplain meadow in response to fine-scale topography - Erzfeld, Lukas; Feilhauer, Hannes; Scholz, Mathias; Hartmann, Timo (ERDKUNDE, 2025)
Floodplains are vital and diverse habitats, providing essential ecosystem services. In Germany, the total surface of floodplain meadows has decreased by over 80% since the 1950s due to human activities such as river channelisation and embankment as well as land use intensification, leading to changes in nutrient and pollutant input. However, effects of these changes on floodplain vegetation remain understudied, primarily due to their recent occurrence. Here we investigate the effects of terrain elevation, flow distance to permanent water bodies (rivers and clay ponds), groundwater-surface distance and thickness of the alluvial clay layer on the plant species composition of the floodplain meadows ‘Papitzer Lachen’ in Northwest Saxony, Germany. We make use of the Ellenberg indicator system to approach statistical results from an ecological point of view. We recorded the vegetation species composition on 20 relevés of 10 m x 10 m (100 m2) each across different floodplain meadow types along an elevation gradient. We classified the plant communities phytosociologically. In addition, we performed an ordination of the plots (detrended correspondence analysis, DCA) and compared the resulting axes to environmental variables using Pearson’s correlation coefficient. As abiotic factors, we used the elevation of each plot measured via DGPS in the field, least cost path to the next water body derived from a digital elevation model, groundwater-surface distance as well as thickness of the alluvial clay layer. We calculated the mean weighted Ellenberg indicator moisture value for each plot and compared it to the DCA results. Three of the stands were classified as Scutellario-Veronicetum longifoliae Walther 1955, eleven as Arrhenatheretum elatioris Braun 1915 and six as a Silaum-silaus-community. The relevés could be roughly separated in two groups along the first DCA axis. The first DCA axis showed significant correlations (p < 0.05) with ground elevation (r = –0.54) and alluvial clay layer thickness (r = –0.68) but no significant correlations with groundwater-surface distance and proximity to water bodies. The weighted mean Ellenberg indicator moisture values significantly correlate with distance to groundwater table (r = –0.59) and confirm a moisture gradient. The main explanatory variable for variation in the vegetation appears to be hydrology. However, variability in water levels which is typical for floodplains has declined. Main reasons are a smaller amplitude of water levels due to river regulation and long periods of droughts. This underlines the strong anthropogenic influence on floodplains. As floodplains are, especially due to their dynamic hydrology, particularly species-rich ecosystems, this study helps to document and understand this diversity to support a conservation value.